Production, Fishing Season and Fishing Ground of the Dominant Fish (Euthynnus affinis, Mene maculata, Leiognathus equulus) Caught by Boat Seine in Palabuhanratu Indonesia - Imron, Mohammad; Baskoro, Mulyono S; Komarudin, Didin (Journal Omni-Akuatika, 2022)
Boat Seine net is a very productive fishing gear in Nusantara Fisheries Port (NFP) Palabuhanratu. Boat Seine was a fishing unit that has the third largest contribution to the provision of fish stocks in 2019, which is 9% of the total production volume of NFP Palabuhanratu after lift net (40%) and longline (35%). The purpose of this study was to analyze the composition of the main catch, productivity, fishing season and to analyse the fishing ground in Palabuhanratu Bay. The type of data collected in this study was quantitative data. Primary data from interviews and field observations of fish landing activities at Palabuhanratu in October 2020 were used to compile this study's data, which included the type of fishing gear used, the composition of the types, and the production of the catch. Secondary data collected were monthly catches and trips made by Boat Seine fishing units. By analyzing the data of Boat Seine net fishing from 2015 to 2019, descriptive analysis method was used to investigate the composition of Boat Seine net catch. The results of the research showed that mackerel (Euthynnus affinis), moonfish (Mene maculata), and ponyfish (Leiognathus equulus) are the dominant fishes caught at the Palabuhanratu waters. The productivity level of Boat Seine net was 348 Kg/Trip in 2015, which increased to 603 Kg/Trip in 2019. The mackerel season occurs around May to September and November. Moonfish fishing season occurs in March, September and October. Ponyfish fishing season occurs in January, March, May, October, November, and December. Boat Seine net fishing grounds in the waters of Palabuhanratu Bay are relatively stationary around the waters of Palabuhanratu Bay.Keywords: CPUE, Fishing Area, Fishing Season Index, Productivity